The new 'New Poverty Agenda' in Ghana: What impact? - Lindsay Whitfield (Danish Institute for International Studies (DIIS), 2009)
This paper describes and explains the impact of the international-driven 'New Poverty Agenda' in Ghana, focusing on the impact of the Poverty Reduction Strategy Papers (PRSPs) adopted by the New Patriotic Party government in power from 2001 until 2008. The paper argues that the New Poverty Agenda has had some impacts, but not they have been limited and not necessarily helpful in achieving long term poverty reduction. The PRSP was seen by the government in Ghana as necessary to secure debt relief and donor resources, and the strategies produced by the government contained broad objectives rather than concrete strategies on how to achieve those objectives and thus had little impact on government actions. The paper discusses what was actually implemented under the NPP government and the factors influencing those actions. It highlights the constraints Ghanaian governments face in pursuing economic transformation within contemporary domestic and international contexts.
Keywords: 330; Armutspolitik; Wachstumspolitik; Ghana